Increasing the Applicability of Strategy Map - Gündoğar, Emin; Aydın, Ayşegül; İpek, Mümtaz; Yurtay, Nilüfer (Archives of Business Research, 2022)
This study proposes a scoring-based structure to make the strategy map feasible. The subjectivity of cause-and-effect relationships is reduced by scoring the map. By map-based reports the strategy map is included to the performance evaluation process. Weighted total method is used in scoring. Causal relations are added in scoring process by strategic path definition. In reporting phase, traffic lamp method is used with the Pareto principle. The scoring-based structure is designed as a synchronization-driven, system-initiating frame. The proposed structure is coded and a software application that generates strategic map and strategic plan reports is developed.